Sowing Moderation Through the Curriculum of Love: The Relevance of Ibn Miskawaih's Middle Path Ethics - Alifa Ihfazna Rafida; Sukino Sukino; Usman Usman (Utan Kayu Publishing, 2025)
Religious moderation is a crucial approach in maintaining social harmony amid religious and cultural diversity in Indonesia, but its implementation still faces serious challenges in the form of intolerance and radicalism. This article examines the relevance of Ibn Miskawaih's concept of the middle path (al-ikhtiyar al-awsat) in the book Tahdhib al-Akhlaq as an ethical foundation for strengthening this moderation, while also proposing a “Curriculum of Love” as a transformative pedagogical approach. The thoughts of emphasizes that moral virtue lies in the balance between two extremes and the purification of the soul (tahdhib al-nafs), which in the context of Islamic education in Indonesia, these values can be integrated through a character-based curriculum to shape an inclusive attitude towards religion. This article argues that the integration of the values of compassion (mahabbah) and moral balance is essential to address the challenge of intolerance, where the “Curriculum of Love” serves as an instrument to internalize religious moderation through an affective approach that goes beyond mere textual understanding. Through a literature review, this study concludes that the synergy between Ibn Miskawaih's middle path ethics and the Curriculum of Love can encourage the creation of “Active Tolerance” and stronger social cohesion, enabling educational institutions to produce a generation that is not only intellectually intelligent but also highly empathetic towards diversity.